2019
DOI: 10.1128/jb.00454-18
|View full text |Cite
|
Sign up to set email alerts
|

PmrC (EptA) and CptA Negatively Affect Outer Membrane Vesicle Production in Citrobacter rodentium

Abstract: Outer membrane vesicles (OMVs) are naturally produced by Gram-negative bacteria by a bulging of the outer membrane (OM) and subsequent release into the environment. By serving as vehicles for various cargos, including proteins, nucleic acids and small metabolites, OMVs are central to interbacterial interactions and both symbiotic and pathogenic host bacterial interactions. However, despite their importance, the mechanism of OMV formation remains unclear. Recent evidence indicates that covalent modifications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
(89 reference statements)
0
24
0
Order By: Relevance
“…This covalent modification is primarily catalysed by specific transferases PmrC and CptA, the expression of which is regulated by PmrAB. Interestingly, PEtN modification contributed to maintenance of OMV integrity, but simultaneously negatively affected the rate of production of OMV by C. rodentium (188).…”
Section: Activation Of Inflammatory Caspases By Extracellular Bacterimentioning
confidence: 99%
“…This covalent modification is primarily catalysed by specific transferases PmrC and CptA, the expression of which is regulated by PmrAB. Interestingly, PEtN modification contributed to maintenance of OMV integrity, but simultaneously negatively affected the rate of production of OMV by C. rodentium (188).…”
Section: Activation Of Inflammatory Caspases By Extracellular Bacterimentioning
confidence: 99%
“…This conundrum could be resolved with the engineering of conditional or inducible deletion strains. In this regard, hypersecretor and hyposecretor strains have been found [36,39,40] (to name just a few), and even rare instances of strains with altered EV morphology [41,42], supporting the view that EVs are not an artifact. One last argument: decreased activity of the Yrb ATP-binding cassette transporter system leads to phospholipid accumulation and an increase in OMV in phylogenetically diverse Gram-negative bacteria [39].…”
Section: Vesicles Are Artifacts Of Lipid Self-aggregation or Debris Fmentioning
confidence: 83%
“…MacDonald and Kuehn showed that oxidative stress-induced OMV production in P. aeruginosa requires the presence of enough B-band-enriched regions in the bacterial outer membrane ( Sabra et al, 2003 ; MacDonald and Kuehn, 2013 ). The role of outer membrane modifications in defending against oxidative stress has also been investigated by Sinha et al (2019) . They observed that in Citrobacter rodentium , as in other enteric bacteria, a two-component system (PmrAB/C) as well as the CptA protein maintain membrane integrity against various stresses.…”
Section: Environmental Stressmentioning
confidence: 99%